Test The Effectiveness Of Several Isolates Of Trichoderma sp. Against White Root Fungus (Rigidoporus microporus) - Mutiara Titik Falahiyah; Syamsul Bahri; Yenni Marnita; Cici Indriani Dalimunthe (University of Prof. Dr. Hazairin, SH, 2023)
This study aims to determine the effectiveness of several isolates of Trichoderma sp. in controlling White Root Fungus disease in rubber plants, knowing the percentage of inhibition of various isolates of Trichoderma sp. against White Root Fungus disease on rubber plants, as well as knowing the growth area of Trichoderma sp. against White Root Fungus disease using Potato Dextrose Agar media with Dual Culture method. Plant disease is a limiting factor on plant growth and development, White Root Fungus disease caused by the pathogen Rigidoporus lignosus has been reported to cause losses to rubber plants Biological control with Trichoderma sp. is disease control by involving the manipulation of beneficial natural enemies to obtain a reduction in population numbers and the status of pests and diseases in the field. This study used the experimental method at the Sungei Putih Research Unit Laboratory using a non-factorial Completely Randomized Design (CRD) consisting of 4 replications. As a treatment, isolate of the endophytic fungus Trichoderma sp. and the isolate tested for antagonism was White Root Fungus. The T2 treatment obtained good effectiveness in suppressing the growth of White Root Fungus with an average inhibition percentage of Trichoderma sp. against White Root Fungus at 8 HSI the highest was obtained in the T2 treatment which was 76.65% and the lowest was in the T0 treatment which was 2.86%. The growth area of Trichoderma sp. the highest at 8 HSI was found in the T2 treatment which was 42.64 cm and the lowest was in the T0 treatment which was 2.86 cm.